Sesoanal Veriation in Primary Productivity from Nanded Region, Maharashtra - Suryawanshi, A. V. (International Journal of Scientific Research in Biological Sciences, 2019)
Study showed that primary productivity status from site A maximum NPP was found in May (1.7 mg/L/hr), minimum in December (0.08 mg/L/hr) and average NPP value was 0.50 mg/L/hr. GPP was maximum in (2.3 mg/L/hr) in May and minimum in January (0.2 mg/L/hr) average GPP value was 0.97 mg/L/hr. CR was maximum in December (1.4 mg/L/hr) and minimum in (0.2 mg/L/hr) in January. Average CR value was 0.55 mg/L/hr in the year Jan 2013- Dec 2013. From site B Maximum NPP value was recorded in May (3.45 mg/L/hr) and minimum in December (0.06 mg/L/hr), average NPP value was 0.45 mg/L/hr. GPP was maximum in May (2.03 mg/L/hr) and minimum in September and November (0.2 mg/L/hr). Average GPP value was 0.86 mg/L/hr. CR was maximum in August (1.7mg/L/hr) and minimum in December (-0.20 mg/L/hr). During the study period average CR value was 0.30 mg/L/hr.